Implementasi Model Pintar Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa - Muhammad Mahdianur, Dessy Dwitalia Sari (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
The problem in this research is the low activity and learning outcomes of students at SDN Kelayan Selatan 3. The purpose of this research is to describe teacher activities, analyze student activities and student learning outcomes. This study uses a qualitative approach with the type of Classroom Action Research (CAR), with 4 meetings. The setting for this research was fourth semester students at SDN Kelayam Selatan 3 for the academic year 2022/2023. The results of the research that has been carried out show that teacher activity at meeting 1 reaches 75% of the "Good" criteria and always increases so that at meeting 4 it reaches 100% of the "Very Good" criteria. Student activity at meeting 1 reached 82%, and increased at meeting 4 reached 100%. The classical completeness of student learning outcomes at meeting 1 reached 48% and also increased until meeting 4 reached 100%. Based on the results of the study, it can be concluded that teacher activities, student activities and learning outcomes in using the PINTAR model have been carried out in accordance with the model steps.